Evolusi Kewarganegaraan di Era Globalisasi dan Digitalisasi (2019-2023) - RIFAL DWI PUTRA; BUDI ARDIANTO (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
Citizenship is the idea of a person's relationship with their country, which includes rights, obligations and roles in their national life. The purpose of this article is to study various aspects of society in a contemporary context, with a particular emphasis on the changes that have occurred in recent years (2019-2023). In this research, secondary data was collected from relevant literature, such as journal articles, books, and research reports. This research method uses a qualitative approach. The results show that the concept of citizenship has evolved to be more inclusive and responsive to global dynamics such as migration, digitalization, and human rights issues.